A multi-hospital analysis of predictors of oral anticoagulation prescriptions for patients with actionable atrial fibrillation who attend the emergency department. (1st October 2016) - Scott-Herridge, Joel A; Seifer, Colette M; Steigerwald, Ron; Drobot, Glen; McIntyre, William F
ABSTRACT: Atrial fibrillation (AF) is the most common arrhythmia and is associated with an increase in the risk of ischemic stroke. The risk of stroke can be significantly decreased by oral anticoagulation (OAC). Our objective was to characterize the filling of OAC prescriptions for patients with actionable AF (new or existing AF with an indication for OAC but not prescribed) and determine the prevalence and predictors of guideline-appropriate therapy at 30 days. This is a multi-hospital, retrospective cohort study of patients who visited the Emergency Department (ED) and had a discharge diagnosis of AF. Patient records were examined to identify demographics, risk factors, and prescription data. Predictors of filling a prescription at 30 days were analyzed. 788 patients with AF were reviewed. 257 patients had actionable AF. Forty one percent (104) had newly diagnosed AF. The mean CHADS2 score was 2 ± 1. At 30 days after discharge, 25.7% of patients filled a prescription for OAC therapy. Large numbers of patients attending the ED have actionable AF, but rates of guideline-directed OAC at thirty days are low. Only a prescription written by the ED physician (OR 9.89) and documentation of stroke risk stratification in the patients' chart (OR 4.09) were associated with the primary outcome.